Screening and Treatment of Perinatal Depression and Anxiety - Agostini, Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint focuses on the assessment, screening and intervention of perinatal depression and anxiety, which have been internationally recognized as relevant mental health problems affecting the whole family system. The contents are of interest for all professionals working in the field of perinatal mental health. Special attention in the reprint is given to three main domains: clinical characteristics of perinatal depression and anxiety in women and men; psychometric properties and usefulness of screening tools; and types of intervention. The first area focuses on the investigation of prevalence, risk factors and predictors of perinatal depression and anxiety, considering different samples of women and/or men, during the prenatal and postpartum period; a glance is also given to perinatal mental health difficulties experienced during the COVID-19 pandemic. The second area is focused on the description of psychometric properties of tools for the detection and screening of perinatal anxiety and depression. This section includes contributions regarding: comparisons among different tools, further validation of already existing questionnaires and validation of new instruments, which could enhance the early detection of depressive and anxiety symptoms. The third area focuses on different approaches of intervention to reduce perinatal depression and anxiety, including gender-transformative interventions to address perinatal mental health and clinical guidelines for the pharmacological management of both depression and anxiety.